Development of axon-target specificity of ponto-cerebellar afferents. - Anna Kalinovsky; Fatiha Boukhtouche; Richard Blazeski; Caroline Bornmann; Noboru Suzuki; Carol A Mason; Peter Scheiffele (PLoS Biology, 2011)
The function of neuronal networks relies on selective assembly of synaptic connections during development. We examined how synaptic specificity emerges in the pontocerebellar projection. Analysis of axon-target interactions with correlated light-electron microscopy revealed that developing pontine mossy fibers elaborate extensive cell-cell contacts and synaptic connections with Purkinje cells, an inappropriate target. Subsequently, mossy fiber-Purkinje cell connections are eliminated resulting in granule cell-specific mossy fiber connectivity as observed in mature cerebellar circuits. Formation of mossy fiber-Purkinje cell contacts is negatively regulated by Purkinje cell-derived BMP4. BMP4 limits mossy fiber growth in vitro and Purkinje cell-specific ablation of BMP4 in mice results in exuberant mossy fiber-Purkinje cell interactions. These findings demonstrate that synaptic specificity in the pontocerebellar projection is achieved through a stepwise mechanism that entails transient innervation of Purkinje cells, followed by synapse elimination. Moreover, this work establishes BMP4 as a retrograde signal that regulates the axon-target interactions during development.